Dimensi Religiusitas Pada Novel Centhini 40 Malam Mengintip SangPengantin Karya Sunardian Wirodono: Kajian Semiotik Dan Implementasinya Sebagai Bahan Ajar Sastra Di SMA - Sumarsono, Sumarsono; Imron Al-Ma'ruf, Prof. Ali; Ngalim M.M., Prof. Dr. Abdul; Hasyim, Dr. Nafron (2017)
The objectives of the study are : (1) to Describe the structure of Centhini novel 40 Malam Mengintip Sang Pengantin by Sunardian Wirodono. (2) To Describe the dimensions of religiousity. (3) To describe the implementation of religious dimentions as the matrial of teaching hiterature at senior High School analysis. The technique of data collection is bibliography technique. Data Validity uses the triangulasi theory and data triangulasi. Data analysis uses semiotic reading that are heuristic and hermeneuto. Heuristik analysis is by giving meaning according to language structure convensionally. Hermeneutic analysis is done by reading repeatedly, giving meaning according to literature convention. The result of the study is that the novel has the instrinsic structures as follows: (1) facts of the story including characters of the story and setting. (2) theme (3) properties of the story are little, angle, figure of speech, tone, symbolism and irony. While religious dimension relative to the life of Javanese society. The are Religious dimension of five which. 1) Believe dimension, the content and context in Centhini novel is about Islamic believ anda Javanese culture. 2) Worship dimension, are obedience to God. 3) Experience dimension are related to the feeling, perception, and harmony experienced. 4) Knowledge dimension refers to the knowledge in doing his believe. 5) Consequence dimension, reflected in the obedience of doing the order and avold the prohibition of God. The implementation of the research in SMA are as follows to as the learning material in teaching literature; to motivate student, to improve language skill, to comprehend culture, as a tool to develop interpretative skill, and as a media to educatie characters. The selection of leteratur media is fitted to the following criteria; linguistic aspect, psikological aspect, and cultural aspect.